Investigating Continuous Delivery on IoT Systems - Pereira, Igor Muzetti; Carneiro, Tiago Garcia de Senna; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
IoT systems have continuous delivery challenges related to development, operations, and hardware teams. Therefore, scientific research and industry professionals have investigated approaches to integrate these areas and overcome these challenges. This study investigates how IoT systems projects adapt to perform Continuous Deliveries (CD) through thirty-one semi-structured interviews and a questionnaire with thirty professionals working in these areas. Inspired by grounded theory, we applied open coding to categorize the results of both interview and questionnaire studies. As contributions, we identified differences in IoT systems development compared to traditional development. We also discuss quality practices used in IoT projects that drive continuous delivery and how teams handle the quest for continuous delivery challenges.